1997
DOI: 10.1002/(sici)1097-0185(199707)248:3<413::aid-ar14>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Larynx-associated lymphoid tissue (LALT) in young children

Abstract: Background Mucosa‐associated lymphoid tissue (MALT) plays a central role in mucosal immunity. Whereas the characteristics and function of MALT in the intestine are well established, almost nothing is known about MALT in the larynx. Methods: In this study we examined the morphology and the lymphocyte subset composition of MALT in the larynges of children who had died of sudden infant death or various defined traumatic or nontraumatic causes. Results: Organized lymphoid tissue was found in the supraglottic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 23 publications
2
40
1
Order By: Relevance
“…It remains to be determined whether LALT is a distinct physiologic entity or a pathologic reaction in response to local infections or other environmental insults. Many children in whom LALT was identified postmortem had died because of sudden infant death syndrome (68,135). Little or no information is available regarding the role of LALT in antigen processing or presentation or the development of immunologic reactivity in the upper airway.…”
Section: Common Mucosal Immune Systemmentioning
confidence: 99%
“…It remains to be determined whether LALT is a distinct physiologic entity or a pathologic reaction in response to local infections or other environmental insults. Many children in whom LALT was identified postmortem had died because of sudden infant death syndrome (68,135). Little or no information is available regarding the role of LALT in antigen processing or presentation or the development of immunologic reactivity in the upper airway.…”
Section: Common Mucosal Immune Systemmentioning
confidence: 99%
“…Here, B and T-lymphocytes, NK cells, and cells of the monocyte/macrophage lineage often form organized mucosa-associated lymphoid tissue (MALT). Kracke et al (1997) analyzed the frequency of laryngeal MALT in young children aged 7 to 671 days. As they found the tissue in nearly 80% of the children investigated and termed it larynx-associated lymphoid tissue (LALT).…”
Section: Discussionmentioning
confidence: 99%
“…Fränkel (1893) describes the frequent occurrence of lymph follicles in the wall of the false vocal folds, which he termed "the laryngeal tonsil." Kracke et al (1997) analyzed the distribution of organized lymphoid tissue at the laryngeal side of the epiglottis and termed the tissue larynx-associated lymphoid tissue (LALT) based on its comparability to gut-associated lymphoid tissue (GALT). The authors also observed the frequent occurrence of lymphoid follicles at the lateral wall of the false vocal folds.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in man [1][2][3] and animals [4,5] show that the larynx does contain immunological tissue. A minor part of this has been reported to be present in the form of epithelial follicles (larynx-associated lymphoid tissue: LALT [1]) in an age-and disease-dependent manner [1,6].…”
Section: Introductionmentioning
confidence: 99%